A Rhizobium loti plasmid involved in nodulation competitiveness - Irisarri, P. (Agrociencia Uruguay, 1997)
Rhizobium loti U226 strain harbors a megaplasmid of about 220 Mdal. To investigate the possible role of this plasmid in the ability of the Rhizobium to form effective nodules, a plasmid-cured derivative strain was constructed using the Tn5-mob-sac system. The wild type and plasmid-cured strain were coupled in their ability to form a symbiosis with Lotus corniculatus. There were no differences in the infectivity or the effectivity of the two bacterial strains. Nevertheless, when lotus plantlets were inoculated with a mixture of strains with and without plasmid, the strain harboring the plasmid occupied the majority of the nodules. This result would indicate that the plasmid from R. loti U226 is implicated in competence for nodule occupation.